Determination of Weights for Criteria with SWARA Technique for Computing Groundwater Quality Index of Various Regions of Navsari District, Gujarat, India - Mr. Hemanshu K. Rana; Dr. Neeraj D. Sharma (Utilitas Mathematica, 2025)
SWARA (Stepwise Weight Assessment Ratio Analysis) is one of the most effective MCDM (Multi-Criteria Decision Making) techniques. The groundwater quality index is constructed using four parameters: TDS, EC, pH, and chlorides. The proportionate weightage of each groundwater quality metric is calculated to calculate the groundwater quality index. In the study, the SWARA approach is used to obtain the relative weightage of groundwater quality characteristics for computing the groundwater quality index of several well sites in the Navsari district of Gujarat, India. To improve groundwater quality in the research region, 48 monitoring and assessment sites were selected. The key criteria for calculating the groundwater quality index were found and defined.